(untitled) (Indian Journal of Animal Production and Management, 2024)
This study aimed to investigate the dairy farming practices and management in Sabarkantha district. A total of 90 livestock owners were randomly selected from six villages representing the Himatnagar, Idar, and Prantij talukas, encompassing three farm size categories based on the number of milch animals: Category A (<10 Milch animals), Category B (10-20 Milch animals), and Category C (>20 Milch animals). The herd composition analysis revealed that cattle were the primary milch animals in the studied farms, with an average total herd strength of approximately 20 cattle and 5 buffaloes. The respondents’ personal characteristics indicated a relatively good level of education, with 32% having attained a graduate level of education. The majority of farmers fell into the 50-65 years age group, and most had more than 10 years of experience in dairy farming. Analysis of milking and healthcare practices revealed that a significant number of farmers employed the knuckling method of milking, which is not recommended. Dry cow therapy and milking parlour usage were less prevalent, but proper drying periods and vaccination and deworming practices were generally followed. Housing practices indicated that most farmers used pacca (concrete) floors and provided adequate light and ventilation. Single-line housing was the most popular system, and drainage facilities were generally adequate. However, milking hygiene practices were found to be suboptimal, with limited use of teat dips or antiseptic udder washing. Overall, the study highlights the need for improvement in milking hygiene practices, along with targeted interventions to enhance dairy management in Sabarkantha district.